DEVELOPING LEARNING MEDIA FOR TEACHING DESCRIPTIVE TEXT WRITING BY USING LECTORA INSPIRE TO THE TENTH GRADE STUDENTS OF TRAVEL AGENCY AND TOURISM PROGRAM IN SMKN 7 MEDAN - Febrasoni Marpaung; Indra Hartoyo; Nora Ronita Dewi (Universitas Negeri Medan, 2019)
This research aimed to develop learning media for teaching writing descriptive text by using Lectora Inspire. This research was conducted by using educational research and development (R&D) proposed by Gall, Gall & Borg method through six phases: gathering data and information, conducting need analysis, designing media, experts validating, revising, and final product. The subjects of this research are 27 students of grade ten of Travel Agency and Tourism program of SMKN 7 Medan which is located in at Jl. STM 12 Sitirejo Medan. The data and data resources were the teacher’s lesson plan, teacher’s interview, and students’ questionnaires result. After getting the last data, the media should be planned to be designed as the students’ needs. The media were developed and had been validated by the experts. The percentage of the media from the experts is 90% that is categorized as very eligible. It can be concluded that interactive learning media is already appropriate to be used as a learning media in teaching writing descriptive text. Keywords: Research and Development (R&D), Learning Media, Descriptive Text, Lectora Inspire, Travel Agency and Tourism program.